Respuesta :
Answer:
see explanation
Step-by-step explanation:
5x + 3y = 6 → (1)
- 4x - 3y = - 3 → (2)
the most efficient method here would be elimination.
add (1) and (2) term by term to eliminate y
x + 0 = 3
x = 3
substitute x = 3 into either of the 2 equations and solve for y
substituting into (1)
5(3) + 3y = 6
15 + 3y = 6 ( subtract 15 from both sides )
3y = - 9 ( divide both sides by 3 )
y = - 3
solution is (3, - 3 )
Answer:
[tex](3,-3)[/tex]
Step-by-step explanation:
[tex]5x + 3y = 6[/tex]
The most efficient method for this equation is elimination.
[tex]x + 0 = 3[/tex]
[tex]5(3) + 3y = 6[/tex]
Substitute x = 3 into any of the equation and solve for y.
[tex]5(3) + 3y = 6[/tex]
[tex]15 + 3y = 6[/tex]
[tex]-15 -15[/tex]
[tex]3y = - 9[/tex]
[tex]\frac{3y}{3}=\frac{-9}{3}[/tex]
[tex]y=-3[/tex]
[tex](3,-3)[/tex]